Informe de pasantia: Alianza estratégica entre la empresa G.A logistic company SAS y la empresa A&V aduanas y valores nivel 2 SAS. - Zapater Cardozo, Karoll Natalia (Universidad Antonio Nariño, 2023)
The practice was carried out in the company G.A LOGISTIC COMPANY SAS. Is a company dedicated to advising in the import sector, advising on logistics and national cargo transportation. The practice was developed in the offices of the city of Bogotá, where from the beginning an induction on the subject was carried out and received nationalization of cargo, in the position of import assistant and functions specific were: organize import documents such as commercial invoice, list packaging, transport document (BL) and other supporting documents required by the agency at the time of the nationalization of the merchandise of its clients. Within the internship report, a preliminary analysis will be carried out, identifying the possible shortcomings on the part of the collaborators in the company GA LOGISTIC COMPANY SAS, in order to know how prepared and qualified they are for the verification and correct delivery of all documents required by the agency customs office with which you currently have a business relationship. The company A&V ADUANAS Y VALORES SAS that throughout the document will called A&V, offered training to employees under the strategic alliance in supporting documents required to avoid further delays and to be able to carry out the nationalization merchandise effectively, this agency being an opportunity for effectiveness of the processes by the collaborators of GA LOGISTIC COMPANY SAS. Given the above, it is considered to make a strategic alliance with the CUSTOMS AGENCY A&V CUSTOMS AND SECURITIES LEVEL 2 SAS, where the The company undertakes to give priority to the consultancies carried out by the company GA LOGISTIC COMPANY SAS, complying with the due presentation of supporting documents for nationalization.